Initial T wave morphology in the chest leads in patients presenting with anterior ST-segment elevation myocardial infarction and its correlation with spontaneous reperfusion of the left anterior descending coronary artery - Dalia Azab; Mohamed Elsayed Zahran; Ahmed Elmahmoudy (International Journal of the Cardiovascular Academy, 2019)
Background: T wave inversion in leads with ST-segment elevation after reperfusion therapy is considered a sign of reperfusion. However, the significance of T wave inversion on presentation before the initiation of reperfusion therapy is unclear. Aim of the Work: The current study aimed to assess whether the initial T wave morphology in the electrocardiographic (ECG) at presentation can predict patency of the left anterior descending artery (LAD) in patients with acute anterior ST segment elevation myocardial infarction (STEMI) before undergoing primary percutaneous coronary interventions (PCIs). Methods: This study included ninety patients who presented to the emergency department with acute anterior ST-elevation MI. We excluded patients with bundle branch block, postcoronary artery bypass grafting patients, patients with paced rhythm, and patients who received thrombolytic therapy. The T wave morphology in the 2 leads with maximal ST-segment elevation on the presenting ECG was identified as one of the three morphologies, positive T waves (T+; initial positive deflection ≥0.5 mm above the isoelectric line), biphasic T waves (T+/−; where the T wave initially showed a positive deflection above the ST segment afterward followed by a negative deflection ≥0.5 mm below the isoelectric line), and negative T waves (T−; where the T wave initially showed a negative deflection ≥0.5 mm below the isoelectric line without showing any initial positive deflection). Then, according to the results of the initial angiography, patients were classified into spontaneous reperfusion (SR) (those with thrombolysis in MI [TIMI] II or TIMI III flow in the infarct-related artery [IRA] prior to intervention) or non-SR (those with TIMI 0 or TIMI I flow in the IRA prior to intervention). Results: Ninety consecutive patients (77 males and 13 females) presented by STEMI and treated by primary PCI at cath lab of Ainshams University Hospitals (a 24/7 tertiary referral center for primary PCI) between January 2015 and March 2016 were included in this study, of which 40 patients (44.4%) had positive T waves (T+), 34 patients (37.8%) had negative T waves (T−), and 16 patients (17.8%) had biphasic T waves (T+/−). Initial angiogram showed that 18 patients had SR and 72 patients had no SR. With regard to T wave morphology, negative T waves were significantly present in SR group (66.7% vs. 30.6%, P = 0.004), whereas positive T waves were predominantly present in non-SR (50% vs. 22.2%, P = 0.033). Conclusions: For SR of LAD in anterior STEMI patients, prior to primary PCI, T wave inversion had a good sensitivity of 66.7%, a specificity of 69.4%, and a good negative predictive value of 89.29%.